2006
DOI: 10.1111/j.1540-8159.2006.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Menstrual Cycle on QT Interval Dynamics

Abstract: Objectives:The aim of this study was to investigate the effects of the menstrual cycle on QT interval dynamics and the autonomic tone in healthy women.Methods: Holter ECGs were recorded in 11 healthy women aged 18-32 years during the follicular and luteal phases of their regular menstrual cycle. The interval from QRS onset to the apex (QaT) and to the end of the T-wave (QeT), the interval between the apex and the end of the T-wave (Ta-e), and RR intervals were measured automatically in the course of 24 hours b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(152 citation statements)
references
References 31 publications
13
133
3
3
Order By: Relevance
“…24 Although electrophysiological experiments using a guinea pig model showed that estrogen prolongs the action potential duration (APD) through the inhibition of IKr, 25 the effect of estrogen on QT interval in humans remains controversial. 26 Progesterone shortens APD, which is mainly attributable to the enhancement of IKs under basal conditions and the inhibition of ICaL under cAMP stimulation, and a computer simulation model using a 50% IKr block indicated a protective effect of progesterone against arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…24 Although electrophysiological experiments using a guinea pig model showed that estrogen prolongs the action potential duration (APD) through the inhibition of IKr, 25 the effect of estrogen on QT interval in humans remains controversial. 26 Progesterone shortens APD, which is mainly attributable to the enhancement of IKs under basal conditions and the inhibition of ICaL under cAMP stimulation, and a computer simulation model using a 50% IKr block indicated a protective effect of progesterone against arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Although several previous studies did not find QT C -interval differences among the different menstrual phases (21,28,29), a recent study analyzing various parameters of cardiac repolarization found that repolarization duration is shorter in the luteal phase than in the follicular phase by about 10 ms (30). The susceptibility of drug-induced arrhythmias also fluctuates considerably during the menstrual cycle in women: the QT C prolongation induced by ibutilide, a class III antiarrhythmic agent, is greatest during menses, intermediate at ovulation, and least in the luteal phase, in which progesterone level is highest (28).…”
Section: Progesteronementioning
confidence: 99%
“…There are reports of increases in the LF/HF ratio, interpreted as indicating increased SNS activity (14-16), increased HF power, interpreted as indicating enhanced PNS activity (17), decreased SDNN and SDANN (12), or no change in time-domain (18) or spectral-domain (19) HRV components during the luteal phase compared with the follicular phase of the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%